Mi Instan Berbasis Pati Sagu dan Ikan Patin serta Pendugaan Umur Simpan dengan Metode Akselerasi - Yusmarini Yusmarini; Usman Pato; S Anirwan; H Siregar (Agricultural Faculty, 2013)
Instant noodle is favorite food in Indonesia. Instant noodle generally made from wheat flour, which is not Indonesian agricultural product. Diversification was needed to solve this problem, and sago starch is potential resource to develop. The research purposed are to produce instant noodle from sago starch and catfish meat fulfilling Indonesia instant noodle quality standard (SNI 01-3551-2000) and to predict instant noodle shelf time using accelerations method. Treatments in this research were SP0 (instant noodle from 100% sago starch), SP1 (instant noodle from 97.5% sago starch and 2.5% catfish meat), SP2 (instant noodle from 95% sago starch and 5% catfish meat), SP3 (instant noodle from 92.5% sago starch and 7.5% catfish meat), SP4 (instant noodle from 90% sago starch and 10% catfish meat), and SP5 (instant noodle from 87.5% sago starch and 12.5% catfish meat). Parameters measured were moisture content before and after frying, protein content, acid value, compactness, and the best treatment continued with shelf time using accelerations method. The result showed that all treatment significantly affected moisture content before and after frying, protein content, acid value and instant noodle compactness. The best treatment was instant noodle from 90% sago starch and catfish meat 10% (SP4) with moisture content before frying 11.29%, moisture content after frying 9.32%, protein content 10.90%, acid value 1.48 mg/g and instant noodle compactness 93.86%. Shelf time for SP4 was 35.81 days.Keywords: instant noodle, sago starch, catfish, accelerated method